Environmental effects of historical charcoal burning associated with water-powered ferrous metallurgy (Mała Panew basin, southern Poland) - Rutkiewicz, Paweł; Malik, Ireneusz (Geology, Geophysics and Environment, 2019)
The main aim of this study was the reconstruction of the environmental changes (identifiable at this stage of research) resulting from large-scale charcoal production for the needs of historical water-powered metallurgy in selected sites in the Mała Panew basin. The identification of the remains of charcoal hearths was carried out by analysing shaded relief models. Shaded relief models were created from data from Airborne Laser Scanning (LIDAR). In order to verify the charcoal hearth remains identified in digital images, ground proofing was carried out. The charcoal hearth remains were subjected to sampling. Fragments of charcoal were extracted from the samples, which were then sent for analysis to identify tree species. In order to determine the age of chosen charcoal hearth remains, 10 charcoal pieces were submitted for radiocarbon dating. The following taxa were identified: Scots pine (Pinus sylvestris), alder (Alnus sp.), birch (Betula sp.), oak (Quercus sp.), Norway spruce / larch (Picea abies / Larix sp.), Silver fir (cf. Abies alba) and ash (Fraxinus excelsior). The taxa identified are dominated by Scots pine (56%). This research demonstrates that valuable wood of deciduous species might have been overexploited at the initial stage of metallurgical production and very quickly exhausted, being replaced by fast-growing coniferous species. The excessive exploitation of the forests might have had negative environmental effects such as the transformation/modification of the species composition of the forest cover, significant deforestation of exploited areas, intensification of floods or the initiation of aeolian transport of sands. All the charcoal hearth remains investigated date to the period from 1677 to 1957 AD.